Manganese(I)‐Catalyzed Dispersion‐Enabled C−H/C−C Activation. Issue 23 (3rd April 2017) - Meyer, Tjark H.; Liu, Weiping; Feldt, Milica; Wuttke, Axel; Mata, Ricardo A.; Ackermann, Lutz
Abstract: C−H/C−C Functionalizations were achieved with the aid of a versatile manganese(I) catalyst. Thus, an organometallic manganese‐catalyzed C−H activation set the stage for silver‐free C−H/C−C transformations with ample substrate scope and excellent levels of chemo‐, site‐, and diastereo‐selectivities. The robust nature of the manganese(I) catalysis regime was reflected by the first C−H/C−C functionalization on amino acids under racemization‐free reaction conditions. Detailed experimental and computational mechanistic studies provided strong evidence for a facile C−H activation and a rate‐determining C−C cleavage, with considerable contribution from London dispersion interactions. Abstract : Amino acid C−H activation : C−H/C−C Functionalizations were achieved with the aid of a versatile manganese(I) catalyst. Thus, an organometallic manganese‐catalyzed C−H activation set the stage for silver‐free C−H/C−C transformations with ample substrate scope and excellent levels of chemo‐, site‐, and diastereo‐selectivities.